Functional analysis of young patients with desmoid-type fibromatosis: Initial surveillance does not jeopardize long term quality of life. Issue 7 (July 2020) - Duhil de Bénazé, G.; Vigan, M.; Corradini, N.; Minard-Colin, V.; Marie-Cardine, A.; Verite, C.; Defachelles, A.S.; Thebaud, E.; Castex, M.P.; Sirvent, N.; Bodet, D.; Mansuy, L.; et al.
Abstract: Background: With recent conservative strategies, prognosis of patients with desmoid-type fibromatosis (DTF) is about function preservation. We analyzed the long-term quality of life (QoL) of pediatric patients with DTF. Methods: All French young patients (<21years) treated between 2005 and 2016 for a DTF in the EpSSG NRSTS-05 study were analyzed. A first wait-and-see strategy was recommended. Patients' QoL was analyzed with the internationally validated Child Health Questionnaire (CHQ). We focused on the relevant subscales scores: physical functioning (PF), role social limitations physical (RP), bodily pain (BP), general health perception (GH) and physical (PhS) and psychosocial (PsS) summary measures. Results: Among the 81 patients, 52 families answered the CHQ (median delay since diagnosis = 6.2years; min2.2-max13.3 years). Median age at diagnosis was 11.5 years. Primary site: limbs (52%), head/neck (27%), or trunk (21%). Five year-Progression Free Survival was 39.1% (95%CI: 27.7–50.5%). As initial management for these 52 patients, 30 patients were first observed (57%), 13 had surgery (25%) and 9 received chemotherapy (18%). Total burden of therapy was exclusive surgery (9pts/18%), exclusive chemotherapy (18pts/35%), surgery + chemotherapy (13pts/25%), chemotherapy + radiotherapy (1 pt), surgery + chemotherapy + radiotherapy (1 pt), wait and see (10 pt). Regarding the parent forms, patients have significant lower PF (86.0vs.96.1; p = 0.03), RP (82.0vs.93.6; p = 0.04), GH (60vs.73; p < 0.005) and PhS (46.2 vs.53; p = 0.02) scores compared to healthy population. Comparison of QoL subscales scores according to initial strategy (wait-and-see vs.surgery/chemotherapy) did not reveal any difference (PF = 87.3vs.84.9; p = 0.80/RP = 83.4vs.78.7; p = 0.72/BP = 78.9vs.78.2; p = 0.95/GH = 59.7vs60; p = 0.97). Similar results were found using the children or adult forms. Conclusions: Initial wait-and-see strategy does not affect long term functional impairment.